Proportion of COVID-19 survivors in 2020-2022 in the Russian population (according to the ESSE-RF3 study) - G. A. Muromtseva; S. A. Shalnova; V. A. Kutsenko; E. M. Filichkina; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; A. V. Kapustina; N. S. Karamnova; M. B. Kotova; S. A. Maksimov; O. B. Shvabskaya; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the proportion of coronavirus disease 2019 (COVID-19) survivors and hospitalization cases of the Russian population for the period 2020-2022, depending on socio-demographic characteristics.Material and methods. The work was performed on random samples of the population aged 35-74 years from 15 regions participating in the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation-3 (ESSE-RF3) study. The examination was carried out from February 2020 to March-April 2022 (n=28718, 47% men).Results. According to a survey of sample participants, the proportion of respondents who had COVID-19 by the spring of 2022 among all surveyed was 26,0%. Among 45-54-year-old respondents, this parameter was maximum (28,0%), while among those aged 65-74-year-old — minimal (22,3%). The following categories of people were more likely to have COVID-19: women (27,9 vs 23,9% of men, p<0,001), persons with higher education (30 vs 22,6% persons without higher education, p<0,001), persons with high income (30,0 vs 24,3% low-income, p=0,002), persons with family (26,6 vs 24,8% single, p<0,001), employed persons (28,4 vs 21,7% non-employed, p<0,001), as well as those living in urban areas (26,5 vs 24,5% country people, p=0,003). But those less likely to have COVID-19 (men, people without higher education, low-income, single, unemployed or rural residents) had more severe disease course. The following categories of people had higher hospitalization rates: men (26,0 vs 20,9% women, p<0,001), patients without higher education (27,1 vs 19,6% those with higher education, p<0,001), non-employed (34,3 vs 18,4% workers), p<0,001) and rural residents (27,2 vs 22,0% of city residents, p<0,001). Hospitalization rate was not associated with the level of income and marital status. However, low-income and single people were more likely to require mechanical ventilation.Conclusion. The results obtained by survey reflect the following population data: the proportion of patients after COVID-19, hospitalization rate and the development of severe acute respiratory failure requiring mechanical ventilation among Russians for the period 2020-2022. This can complement the population data demonstrated by state statistics. Special attention from the healthcare system, both during treatment and prevention of COVID-19, requires males, people aged ≥65 years, low-income people, single people (widowers, divorced), unemployed people (pensioners, disabled people, nonemployed), rural residents and people without higher education.